Sociological conceptions of happiness and its implications for psychotherapy and public policy - Shaw, Ian; Middleton, Hugh (OMICS International, 2015)
This paper critiques the usefulness of cognitive-behavioural therapy, which is often seen as a means of redressing the loss of community and friendship networks within society. Therapy in this context they runs the danger of becoming an Iatrogenesis at worst and just another `technology of mood’ at best. In this paper we develop the critiques made elsewhere and provide a more nuanced argument that considers a wider range of psychological therapies. While all psychological therapies operate at an individual level, there are wide differences in the epistemological stances taken by differing therapeutic schools. Cognitive-behavioural therapy focuses on the idea of dysfunctional thinking within the individual, psychoanalytic therapy focuses upon developmental legacies, whereas person-centred therapy focuses on currently active social influences. In this form one to one therapy can be a route to change which is compatible with our sociological critique. However, the broader criticism that psychological therapies attempt to compensate for breakdowns in friendship and social networks remains. Furthermore reviews of psychotherapeutic outcome data and qualitative enquiry both point to the experience of authentic relationship rather than psychotherapeutic technique as the major determinant of outcome. Preventing social dislocation rather than trying to repair it post hoc should be the goal. This would beg a wider range of questions such as; what does social isolation actually mean in contemporary western society and what does this mean for people with mental health problems in particular? What are the various ways in which social networks provide support functions and what may be missing in an individual’s life and then what can be done to try and compensate for that lack?